Haemorrhagic Bullous Lesion in Henoch-Schonlein Purpura - Renata Prameswari; Diah Mira Indramaya; Sawitri Sawitri (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Henoch-Schonlein purpura (HSP) is a vasculitis of the small vessels and the most common type of vasculitis in children. Vesicles and haemorrhagic bullae were thought to be rare in HSP and maybe difficult to diagnose. Purpose: To describe the rare case of haemorrhagic bullous lesion in HSP. Case: A 15-year-old Javanese girl was admitted to Dr. Soetomo General Hospital Surabaya with one week history of multiple haemorrhagic blisters on her extremities, accompanied with joint pain, abdominal pain, and severe nausea. Firstly, it’s only a few redness patches then become numerous and changed to haemorrhagic blisters. A dermatological examination shown multiple bullae and vesicles on multiple palpable erythematous purpura. There were hypokalemia on laboratory examination and histopathological examination concluded a leukocytoclastic vasculitis. Discussion: Fluid balance, oral corticosteroid, oral antihistamine, antiemetic injection, and potassium correction were administered to the patient. Dexamethasone was discontinued because there was a presence of melena. Symptomatic treatment was given and significantly improvement was achieved in one month after treatment. Conclusion: Henoch-Schonlein purpura is diagnosed based on history, physical, clinical, and histopathological examination. Vesicles and haemorrhagic bullae are rare in HSP, and it does not seem to have any prognosis value in the outcome of HSP. Key words: Henoch-Schonlein purpura, haemorrhagic bullous lesion, small vessel vasculitis.